TEACHERS’ CREATIVITY TO HELP STUDENTS IN ACHIEVING DAILY ENGLISH CONVERSATION GOAL OF D-BEATS (DYNAMIC – BOARDING ENGLISH ARABIC TAHFIDZ SCHOOL) - Lestari, Dwi April; Asyhar, Wildan Isna (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2022)
D-BEATS is a boarding school which activity is learning tahfidz and the language use either English or Arabic in daily conversation. English use is primary language in this research. In boarding school exists a class of morning conversation which class is giving vocabularies. The English teachers teach English in morning conversation by questioning and role-play. The teachers use those ways in order to make the students usual to make question and appear new vocabularies in any activity. In process of daily conversation, the students face the challenges such forget and limit the vocabulary, a chance to speak Indonesian if out of monitoring, and the basic challenge is when another person speaks Indonesian other person will respond in Indonesian too. English teacher helps the students to speak English in daily activity by activating the language department. It works like each student becomes a spiyer to spy about the use of English in whole daily activity. For whomever who breaks the language they will be noted by spiyer and reported to the language department to get punishment. The environment in boarding of D-BEATS like other teachers who live in boarding like Tahfidz teacher, Arabic teacher, and canteen keeper, they also try to service the students with English. The learners’ reflection after getting the teachers’ creativity shows that the students’ effort to speak English as often in daily conversation, speak English every day, every time, except free day language, feel free to speak English.